2008
DOI: 10.1111/j.1442-2042.2008.02197.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life after radical prostatectomy in Japanese men: A 5‐Year follow up study

Abstract: Objectives: To measure health-related quality of life (HRQOL) after radical prostatectomy (RP) in Japanese men with localized prostate cancer. Methods: A total of 154 patients who underwent RP were included in this 5-year longitudinal survey. The Short Form 36-Item Health Survey, the University of California, Los Angeles, Prostate Cancer Index and the International Prostate Symptom Score questionnaires were administered at diagnosis and nine times afterwards. Results: Patients undergoing RP showed problems in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 34 publications
5
54
1
Order By: Relevance
“…In the current study, 44% of the patients did not return to baseline values, which was consistent with other reports of similar scores in the recovery of urinary control after surgery [6,16]. We compared these results with those from our previous study that assessed the patients with early prostate cancer [17]. The previous study showed higher rates of urinary control, with more than 80% of the patients recovering to the baseline urinary function score at 60 months.…”
Section: Discussionsupporting
confidence: 94%
“…In the current study, 44% of the patients did not return to baseline values, which was consistent with other reports of similar scores in the recovery of urinary control after surgery [6,16]. We compared these results with those from our previous study that assessed the patients with early prostate cancer [17]. The previous study showed higher rates of urinary control, with more than 80% of the patients recovering to the baseline urinary function score at 60 months.…”
Section: Discussionsupporting
confidence: 94%
“…It is important to emphasize that urinary incontinence after RP increases with age (Stanford et al 2000). Our previous survey revealed that 88% younger men (younger than 60) reached baseline urinary function at 24 months postoperatively using the same methods (Namiki et al 2009). In the current study, however, only 54% of patients returned to baseline values, which was less than that observed in younger RP subjects.…”
Section: Discussionmentioning
confidence: 94%
“…While oncological and functional outcomes are routinely evaluated, quality of life (QoL) is often overlooked. Namiki et al (2009) have studied the effect of open RP on QoL using the Short Form 36-Item Health Survey (SF-36) and other prostate-specific questionnaires, and showed that by 5 years most men had returned to baseline levels of QoL. White et al (2008) compared QoL outcomes for patients from the CapSURE database with locally advanced prostate cancer undergoing different treatments, and showed that all treatments were associated with reductions in QoL scores, although they were unable to determine the 'best' treatment with regards to QoL.…”
Section: Results Of Different Types Of Rpmentioning
confidence: 99%